Histological Findings in Infected and Noninfected Second Stage Revision Knee Arthroplasties - Uchihara, Yoshinobu; Inagaki, Yusuke; Munemoto, Mitsuru; Tanaka, Yasuhito; Athanasou, Nicholas (The Journal of Knee Surgery, 2019)
Tissues from a periprosthetic joint infection (PJI) of the knee contain a heavy neutrophil polymorph (NP) infiltrate (> 5 NPs per high-powered field [HPF] by Musculoskeletal Infection Society [MSIS] criteria). PJI of the knee can be treated by a two-stage procedure and our aim was to determine whether the MSIS histological criteria for PJI diagnosis are valid in a second-stage revision knee arthroplasty. Periprosthetic tissues from 45 second-stage revision knee cases were analyzed histologically by hematoxylin–eosin and chloroacetate esterase (CAE) staining for the identification of NPs. The number of NPs was determined semiquantitatively and results correlated with the microbiological and clinical findings. In 9 of the 45 cases, an organism was cultured in two or more samples, meeting MSIS microbiological criteria for a definite diagnosis of PJI; histologically, seven of these cases contained > 5 per NPs per HPF on average, with the remaining two cases containing 1 NP and 2 NPs per HPF. In noninfected second-stage revisions, NPs were not seen in 30 cases with 6 cases showing less than 1 NP per HPF on average. The sensitivity, specificity, accuracy, and positive and negative predictive values of MSIS histological criteria (> 5 NPs per HPF) to diagnose PJI were 78%, 100%, 96%, 100%, and 95%, respectively. MSIS histological criteria for the diagnosis of PJI are valid for most but not all infected second-stage revision knee arthroplasties. Correlation of histology with clinical, microbiology and other laboratory findings is required to establish a diagnosis of PJI in second-stage revision knee arthroplasties.
Keywords: arthroplasty; infection; histology; diagnosis; second stage